Developing a rapid assessment framework for China earthquake disaster losses: insights from physical simulations of the Yangbi earthquake - Yilong Li; Zhenguo Zhang; Xiaofei Chen (npj Natural Hazards)
Abstract Earthquakes remain unpredictable and pose significant challenges to disaster preparedness. This study develops a rapid assessment framework for earthquake disaster losses based on physical simulations, demonstrated through analysis of the 2021 Ms 6.4 Yangbi earthquake. A finite fault source based on observed data is employed on a GPU-accelerated 3D strong ground motion simulation platform. The computational process considers the effects of 3D heterogeneous velocity structure and terrain. Subsequently, this data is incorporated into a mathematical model for earthquake disaster loss assessment derived from historical statistics, evaluating emergency response levels, fatalities, and economic losses. The inclusion of teleseismic data into this framework underscores its extensive applicability for rapid loss assessments, even in regions lacking local seismic data. Through comparisons with station observation waveforms and government-reported loss, the validity and practicality of the framework were substantiated. It plays a vital role in assisting emergency decisions, optimizing resource allocation, and further mitigating losses.